Case Report: A Case of Pediatric Catatonia: Role of the Lorazepam Challenge Test - Ridgeway, Laura; Okoye, Albert; McClelland, Ian; Dhossche, Dirk; Kutay, Deniz; Loureiro, Mario (Frontiers in Psychiatry, 2021)
A case of a 12-year-old boy who developed catatonia is presented. He had no previous psychiatric history but has a family history of affective disorder. An extensive medical work-up was negative. Despite a negative lorazepam challenge test, lorazepam was titrated up to 24 mg per day with resolution of most catatonic symptoms. The case highlights an important point in the management of catatonia that may be a source of confusion, i.e., a positive lorazepam challenge test corroborates the diagnosis of catatonia, however, a negative lorazepam challenge test does not negate the diagnosis of catatonia and subsequent focused benzodiazepine treatment may still be effective.